Cooperative Catalysis toward Oxygen Reduction Reaction under Dual Coordination Environments on Intrinsic AMnO3‐Type Perovskites via Regulating Stacking Configurations of Coordination Units. Issue 50 (12th November 2020) - Zhao, Chunning; Zhang, Xilin; Yu, Meng; Wang, Ansheng; Wang, Linxia; Xue, Lina; Liu, Jieyu; Yang, Zongxian; Wang, Weichao
Abstract: It remains challenging for pure‐phase catalysts to achieve high performance during the electrochemical oxygen reduction reaction to overcome the sluggish kinetics without the assistance of extrinsic conditions. Herein, a series of pristine perovskites, i.e., AMnO3 (A = Ca, Sr, and Ba), are proposed with various octahedron stacking configurations to demonstrate the cooperative catalysis over SrMnO3 jointly explored by experiments and first‐principles calculations. Comparing with the unitary stacking of coordination units in CaMnO3 or BaMnO3, the intrinsic SrMnO3 with a mixture of corner‐sharing and face‐sharing octahedron stacking configurations demonstrates superior activity ( E half‐wave  = 0.81 V), and charge–discharge stability over 400 h without the voltage gap (≈0.8 V) increasing in zinc–air batteries. The theoretical study reveals that, on the SrMnO3 (110) surface, the active sites switch from coordinatively unsaturated atop Mn (*OO, *OOH) to Mn–Mn bridge (*O, *OH). Therefore, the intrinsic dual coordination environments of Mn–Ocorner and Mn–Oface enable cooperative modulation of the interaction strength of the oxygen intermediates with the surface, inducing the decrease of the *OH desorption energy (rate‐limiting step) unrestricted by scaling relationships with the overpotential of ≈0.28 V. This finding provides insights into catalyst design through screening intrinsic structures with multiple coordination unit stacking configurations. Abstract : The intrinsic superior oxygen reduction reaction activity of SrMnO3 stems from mixed cubic and hexagonal stacking configurations, introducing cooperative catalysis under MnOcorner and MnOface coordination environments. The filling of the Ovacancy in the Ocorner site influences the charge distribution in the Oface, which modifies the surface interaction strength with intermediates and triggers active site migration from atop Mn (*OO, *OOH) to MnMn bridge (*O, *OH).